Решить уравнение: (3x+2)(3x-4)-(2x+3)(3x-1)+(3x+1)(x-4)

0 голосов
42 просмотров

Решить уравнение: (3x+2)(3x-4)-(2x+3)(3x-1)+(3x+1)(x-4)


Алгебра (115 баллов) | 42 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1)9x²– 12x + 6x – 8 – (6x²– 2x + 9x – 3) + 3x²– 12x + x – 4;
9x²– 12x + 6x – 8 – (6x² + 7x – 3) + 3x²– 12 + x – 4;
9x²– 12x + 6x – 8 – 6x²– 7x + 3 + 3x²– 12 + x – 4;
6x²– 24x – 9
х(1) + х(2) = – 4
х(1) • х(2) = – 1,5 = – 1 1/2 = – 3/2 = – 9/6
х(1) = 8.
х(2) = – 12.

(44 баллов)
0 голосов

1)9x²– 12x + 6x – 8 – (6x²– 2x + 9x – 3) + 3x²– 12x + x – 4;
9x²– 12x + 6x – 8 – (6x² + 7x – 3) + 3x²– 12 + x – 4;
9x²– 12x + 6x – 8 – 6x²– 7x + 3 + 3x²– 12 + x – 4;
6x²– 24x – 9=0
х₁+х₂=-4
х₁*х₂=-9/6
х₂=8
х₁=-12

(17.6k баллов)